The effect of implants on gain of heifers grazing native grass - Brazle, F.K.; Cook, D.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three hundred-ninety crossbred heifers were allotted randomly to one of three implant treatments: 1) Implus- H®, 2) Synovex-H®, and 3) Ralgro®. The heifers grazed native grass pastures for 122 days, stocked at 4 acres per head. The heifers receiving the Implus-H tended to gain faster (P<.12) than the Ralgro heifers. No difference in gain occurred between the Implus-H and Synovex-H heifers.
Keywords: Beef; Implant; Grazing cattle; Native grass